Pattern matching algorithm for artificial to natural DNA codes of a dementia brain - Shamsudin, Ahmad Faizul; Azhar, Md. Tahir; Salih, Falah; Md. Noon, Hazizan; Ahlan, Abdul Rahman; Suhaimi, Mohd Adam; Bal-Fagih, Zain; Ibrahim, Nurnajhan; Mohd. Badri, F (Institute of Electrical and Electronics Engineers Inc. (IEEE), 2008)
Natural to natural DNA.sequencing has achieved high degree of accuracies in existing visualization and alignment techniques. This Dementia Brain research on animals used motif matching techniques in the natural to computer generated artificial DNA sequencing. The natural DNA sequence of dementia brain in a rat was extracted and visualized at the DNA analytical laboratory. The artificial DNA sequences are generated by a Dementia-Brain software at the brain-computing laboratory. The use of DNA Thumbprint motif pattern matching showed significant levels of fitness in the natural-to-artificial as in the natural-to-natural DNA sequencing. The matching between the laboratory extracted DNA and the computer generated DNA will enhance the use of brain-computing in predicting neural degradation such as dementia.